Generalized Nested Array: Optimization for Degrees of Freedom and Mutual Coupling - Shi, Junpeng; Hu, Guoping; Zhang, Xiaofei; Zhou, Hao (IEEE communications letters, 2018)
In this letter, we propose a generalized nested array (GNA) with two flexible co-prime factors for enlarging the inter-element spacing of two concatenated uniform linear subarrays. It is shown that both the prototype nested array and generalized co-prime array can be interpreted as special cases. The closed-form expressions for the range of consecutive lags and the number of unique lags are derived for any given factors. After optimization, GNA has the same number of degrees of freedom as (super) nested array but with reduced mutual coupling. Numerical simulations prove the superiority of proposed configuration using compressed sensing algorithm.